Faktor Penentu dan Dampak dari Keadilan Organisasi: Perspektif Manajemen Perubahan - Yuliawati, Ananda Karisma; Novita, Wisandra; Zaitul, Zaitul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study examines servant leadership's effect on organizational justice and commitment to change among civil servants (ASN) at the Bawaslu office of Padang City. The research employs a quantitative method by distributing questionnaires to 52 respondents. The results show that servant leadership positively and significantly affects organizational justice, indicated by a p-value of less than 0.01. Organizational justice was also found to impact substantially commitment to change, as supported by statistical analysis. However, servant leadership does not have a significant direct influence on commitment to change. This study concludes that organizational justice is important in enhancing commitment to change, while servant leadership can strengthen perceptions of justice among organizational members. These findings provide practical implications for leaders to focus on applying justice principles in leadership processes to improve employee commitment to organizational change.